Recent Trends in Maintenance Costs for Façades Due to Air Pollution in the Oslo Quadrature, Norway - Terje Grøntoft (Atmosphere, 2019)
This study assesses changes since 1980 in the maintenance cost of the façades of the historical 17th to 19th century buildings of the Oslo Quadrature, Norway, due to atmospheric chemical wear, including the influence of air pollution. Bottom up estimations by exposure−response functions for an SO2 dominated situation reported in the literature for 1979 and 1995 were compared with calculations for the present (2002−2014) multi-pollutant situation. The present maintenance cost, relative to the total façade area, due to atmospheric wear and soiling was found to be about 1.6 Euro/m2 per year. The exposure to local air pollution, mainly particulate matter and NOx gases, contributed to 0.6 Euro/m2 (38%), of which the cost due to wear of renderings was about 0.4 Euro/m2 (22%), that due to the cleaning of glass was 0.2 Euro/m2 (11%), and that due to wear of other façade materials was 0.07 Euro/m2 (5%). The maintenance cost due to the atmospheric wear was found to be about 3.5%, and that due to the local air pollution about 1.1% of the total municipal building maintenance costs. The present (2002−2014) maintenance costs, relative to the areas of the specific materials, due to atmospheric wear are probably the highest for painted steel surfaces, about 8−10 Euro/m2, then about 2 Euro/m2 for façade cleaning and the maintenance of rendering, and down to 0.3 Euro/m2 for the maintenance of copper roofs. These costs should be adjusted with the importance of the wear relative to other reasons for the façade maintenance.